The safety of care focused on patient identity: an observational study - Nitro, Martina; Romano, Rita; Marletta, Giuseppe; Sollami, Alfonso; La Sala, Rachele; Artioli, Giovanna; Sarli, Leopoldo (Acta Biomedica Atenei Parmensis, 2021)
Background and aim: Healthcare organizations, in order to reduce errors and extend the number of safe practices, are looking for possible solutions to enhance the clients’ health quality care and trying to spread the culture of safety healthcare. Although in the literature the field of research “patient safety” is very debated, there are few empirical studies that investigate about the strategies undertaken by nursing students for the patients identification process during their care pathway. The aim of this study is to investigate the knowledge of the Ministerial Recommendation No. 3/2008 among nursing students, a specific Italian directive that aims to guarantee the safety of cares.Methods: A four-weeks single-center observational study was conducted, involving a convenient sample of 112 students of the 2nd and 3rd  year of the Nursing Course Degree of the University of Parma. The survey was conducted using an ad-hoc questionnaire.Results: The use of the identification wristband is considered one of the most important strategy to make sure the patient identification; unfortunately it is in practice used just in few occasions and only when performed specific procedures; it is furthermore noted that patients are not enough informed about the use and finalities of the identification wristband.Conclusions: Considering the importance of the patient identification process to guarantee the  safety of cares, the results produced, suggest that this investigation field deserves further insights in order to collect more substantial data and expand knowledge on the specific subject, so as to fill  knowledge gaps and sensitize nursing students to the correct use of the identification wristband.